Grants Scheme : 2008 Project Summaries. (Australian Learning and Teaching Council (ALTC), 2008)
The Grants Scheme enables the Australian Learning and Teaching Council Limited (ALTC) to realise its designated responsibility to provide grants for academics and professional staff to investigate, develop and implement innovations in learning and teaching, and to develop leadership capabilities. This report provides summaries funded by the scheme in 2008.